If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(3x+4=2x+8+4x
We move all terms to the left:
2(3x+4-(2x+8+4x)=0
We add all the numbers together, and all the variables
2(3x+4-(6x+8)=0
| 11x^2+x=10=0 | | 0.23x=7.86 | | 6^(2x)=36^2 | | 3÷(x+8)=6 | | -2x2+3x-2=-8x2-2x+2 | | 7/y-1/6=14 | | k+2.1=4.9 | | (x+8)÷3=6 | | 7/y-1/6)=14 | | 6-(-5)=5x-3 | | -6c^2+7=0 | | -7.4+5.3x=1.5 | | -5=-(y+1)-1 | | 6x^2+45=0 | | 7/8(-32-48x)=36=2/3(-33x-18)-10x | | -18=(7-n)(3) | | 3x+4=128 | | 4.5x^2−3x+15=0 | | -4+x/9=1 | | 8=2.3+h | | X^3-3x^2-2x+45=0 | | 7n-4/3=8 | | t/18=2/t | | 1.25x+18=2x | | 1/2(12m-8)=26 | | 7x-6=14x+7 | | -5x+4=-2(x+2) | | 3.4f=-44.2 | | y+13/49=-40 | | 2(-2x-3)=3(-x+2) | | 6/5v+8/v=1 | | y=13/49=-40 |